Radiological Response to Capecitabine and Temozolomide in an Elderly Patient with Metastatic Leiomyosarcoma: A Case Report - Suayib Yalcin; Can Kilinc; Taha Koray Sahin; Omer Dizdar (Journal of Clinical Medicine, 2026)
Metastatic leiomyosarcoma (LMS) is characterized by limited treatment options beyond first-line therapy, and cross-resistance among cytotoxic agents is often assumed to exist. However, differential sensitivity to distinct chemotherapy mechanisms may exist. We report the case of an 81-year-old woman diagnosed with metastatic LMS of unknown primary origin presenting with extensive hepatic and pulmonary involvement. Following eight cycles of first-line gemcitabine plus docetaxel, the patient achieved stable disease without objective tumor shrinkage. Given this limited response, a significant radiological response to subsequent therapy was not anticipated. Second-line oral capecitabine and temozolomide (CAPTEM) was initiated, resulting in a marked radiologic regression at four months, with reductions in hepatic metastases and pulmonary nodules and no new lesions. Treatment was well tolerated, with no grade 3–4 toxicities. This case demonstrates a differential response to gemcitabine-based therapy and sensitivity to alkylating agents in LMS, supporting a more individualized, mechanism-driven treatment sequencing approach.